2014
DOI: 10.36457/gizindo.v34i1.102
|View full text |Cite
|
Sign up to set email alerts
|

Efek Pemanfaatan Program Pemantauan Dan Promosi Pertumbuhan Terhadap Status Gizi Balita Di Kota Cirebon

Abstract: Efek pemanfaatan program pemantauanLia Nurcahyani, dkk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
1
0
1
Order By: Relevance
“…Prior observational studies in Cirebon and Demak, Indonesia, showed that growth monitoring program could significantly affect children's wellbeing and supportive environment. The influencing factors of growth monitoring program including policymakers, community, and cadres/healthcare practitioners as providers are needed (Sahanggamu et al, 2017;Nurcahyani, Hakimi, & Sudargo, 2011). Furthermore, political commitment, investment, strengthening of health systems, and training and supervision for providers must be evaluated and improved (Ashworth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Prior observational studies in Cirebon and Demak, Indonesia, showed that growth monitoring program could significantly affect children's wellbeing and supportive environment. The influencing factors of growth monitoring program including policymakers, community, and cadres/healthcare practitioners as providers are needed (Sahanggamu et al, 2017;Nurcahyani, Hakimi, & Sudargo, 2011). Furthermore, political commitment, investment, strengthening of health systems, and training and supervision for providers must be evaluated and improved (Ashworth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pengukuran status gizi santri Pengukuran status gizi ini penting dilakukan untuk memberikan informasi kepada para santri bahwa penimbangan berat badan dan pengukuran tinggi badan sangat penting dilakukan setiap 6 bulan sekali untuk memantau pertumbuhan mereka serta memantau status gizi [9]. Program yang direkomendasikan oleh WHO dan UNICEF untuk menurunkan giziburuk dan kurang adalah program pemantauandan promosi pertumbuhan/growth monitoring and promotion (GMP) program, yang dilaksanakan melalui posyandu.Program pemantauan dan promosi pertumbuhan sebagai skrining program untuk mencegah gizi kurang melalui deteksi dini gagal tumbuh dapat berupa pemantauan pertumbuhan dengan outcome penurunan gizi kurang/ buruk,kesakitan dan kematian, serta promosi pertumbuhan dengan outcome peningkatan perilaku/pola asuh ibu (pengetahuan, sikap dan tindakan) [10].…”
Section: Gambar 3 Santri Mendegarkan Materi Penyuluhanunclassified